Analisis Peran Persepsi Harga Dan Brand Image Terhadap Purchase Decision Produk Sepatu Dengan Merek Vans - Irma Maria Dulame; I Wayan Gede Antok Setiawan Jodi; Ita Nurcholifah; Sarwo Eddy Wibowo; Abdurohim Abdurohim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to determine the effect of brand image and price perception partially or simultaneously on purchasing decisions. The type of research used is quantitative associative research. The subjects of this study were consumers of Vans shoes with a sample of 115 respondents. The data collection method uses a questionnaire. Analysis of the data used is descriptive analysis, the classic assumption test and multiple linear regression analysis. Hypothesis testing using the T test, F test, and R2Test. In this study it can be seen that partially, the brand image variable (X1) and price perception (X2) each have a significant effect on purchasing decisions (Y). Simultaneously, brand image (X1) and price perception (X2) significantly influence purchasing decisions (Y). The coefficient value of R2 by looking at the value of R Square 0.731 or 73.1%. Keywords: Brand Image, Price Perception, Purchase Decision